2005
DOI: 10.1098/rspb.2004.2988
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of cooperation by generalized reciprocity

Abstract: The evolution of cooperation by direct reciprocity requires that individuals recognize their present partner and remember the outcome of their last encounter with that specific partner. Direct reciprocity thus requires advanced cognitive abilities. Here, we demonstrate that if individuals repeatedly interact within small groups with different partners in a two person Prisoner's Dilemma, cooperation can emerge and also be maintained in the absence of such cognitive capabilities. It is sufficient for an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(177 citation statements)
references
References 22 publications
12
163
0
2
Order By: Relevance
“…Consequently, despite the birds having made some errors or cheated occasionally, their propensity to forgive allowed mutual cooperation to be easily re-established in this treatment. Thus, our study demonstrates that animals can adjust their behavioural decisions not only to the identity of the partner they interact with, but also to their past experience, and suggests that reciprocal altruism might be more common among non-human animals than originally thought (Hammerstein 2002;Stevens & Hauser 2004; but see Pfeiffer et al 2005;Krams et al 2008). To date, however, the importance of reciprocity has probably been underestimated to the detriment of simpler mechanisms, because most controlled experiments that have failed to find cooperation imposed unrealistic constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, despite the birds having made some errors or cheated occasionally, their propensity to forgive allowed mutual cooperation to be easily re-established in this treatment. Thus, our study demonstrates that animals can adjust their behavioural decisions not only to the identity of the partner they interact with, but also to their past experience, and suggests that reciprocal altruism might be more common among non-human animals than originally thought (Hammerstein 2002;Stevens & Hauser 2004; but see Pfeiffer et al 2005;Krams et al 2008). To date, however, the importance of reciprocity has probably been underestimated to the detriment of simpler mechanisms, because most controlled experiments that have failed to find cooperation imposed unrealistic constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Models of the repeated Prisoner's Dilemma have shown that the strategies most likely to lead to stable cooperation are those in which individuals copy the previous behaviour of their partners, cooperating when they do and ceasing to cooperate if their partners defect ('tit-for-tat'), especially if cooperative players occasionally forgive defectors ('generous' tit-for-tat [7]). Recent models have extended the original two-partner dyad to encompass larger cooperative networks, considering situations in which many individuals can repeatedly interact to trade commodities under conditions that are less restrictive and more socially complex than those envisioned by original solutions of the Prisoner's Dilemma game [104]. Several rstb.royalsocietypublishing.org Phil.…”
Section: (B) Reproduction By Subordinatesmentioning
confidence: 99%
“…Generalized reciprocity results when B helps C because A helped B independently of the identity of individuals (Hamilton and Taborsky, 2005a;Pfeiffer et al, 2005;Rutte and Taborsky, 2007). There is evidence for generalized reciprocity in humans (Yamagishi and Cook, 1993) and rats (Rutte and Taborsky, 2007).…”
Section: Generalized Reciprocitymentioning
confidence: 99%